Zone Refinement of Germanium Crystals. (April 2015) - Yang, G; Guan, Y T; Jian, F Y; Wagner, M D; Mei, H; Wang, G J; Howard, S M; Mei, D M; Nelson, A; Marshal, J; Fitzgerald, K; Tenzin, C; et al.
Abstract: Purification of commercial germanium with an impurity level of ∼10 13-14 cm -3 was successfully conducted in two-step zone refining process under an undiluted high-purity hydrogen gas atmosphere. Results for the first step conducted in graphite boats yielded ingots with an impurity level of ∼10 12 cm -3 near the center of the 60 cm long ingots. These center portions were collected and subsequently zone refined in a high purity quartz boat to reach a purity level of ∼10 11 cm -3 . The best material achieved in a one step process employing a carbon-coated quartz boat yielded material of purity 8×10 11 cm -3 .